142k views
3 votes
Help on both questions please!! Ty

Help on both questions please!! Ty-example-1
User Maryokhin
by
4.8k points

1 Answer

6 votes
First question’s answer:
Since angle A = Angle E
Therefore, Angle B (=x) = Angle D
B = X
D = 66
By replacement B = X = D = 66
So, B = 66
Answer is (A)
-------------
Second question’s answer:
Since Angle F = 63 & Angle C = (3X + 3)
Therefore, Angle F = Angle C
63 = (3X + 3)
Add (-3) into each side
63 + (-3) = (3X + 3) -3
3x + -3x = 0
63 + -3x = 3 + 0
63 + -3x = 3
Now, Add '-63' to each side of the equation
63 + -63 + -3x = 3 + -63
63 + -63 = 0
0 + -3x = 3 + -63
-3x = 3 + -63
3 + -63 = -60
-3x = -60
Divide each side by '-3'
x = 20
So, X angle value is 20 (X=20)
The answer is (C)


Good luck!
User Cory Madden
by
5.6k points